FORMATION OF THE CULTURE OF PEDAGOGICAL COMMUNICATION FUTURE TEACHERS IN DIALOGICAL EDUCATION SITUATIONS IN HIGHER EDUCATION CLASSES (Pedagogy of Higher and Secondary Education, 2022)
The author emphasizes the necessity of using the pedagogical technology as an effective means of formation of the culture of pedagogical communication of future teachers.
Keywords: pedagogical technologies; pedagogical dialogue